2017
DOI: 10.1007/s00262-017-2077-9
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin receptor antagonist alters pancreatic cancer microenvironment and increases efficacy of immune checkpoint antibody therapy in mice

Abstract: Advanced pancreatic ductal adenocarcinoma (PDAC) has typically been resistant to chemotherapy and immunotherapy; therefore, novel strategies are needed to enhance therapeutic response. Cholecystokinin (CCK) has been shown to stimulate growth of pancreatic cancer. CCK receptors (CCKRs) are present on pancreatic cancer cells, fibroblasts, and lymphocytes. We hypothesized that CCKR blockade would improve response to immune checkpoint antibodies by promoting influx of tumor-infiltrating lymphocytes (TILs) and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Apart from their proliferative role on cancer cells, CCK receptors have been identified on pancreatic stellate cells [40] and fibroblasts [41]. Proglumide treatment decreases tumor-associated fibrosis in mouse models of pancreatic cancer [24,36,42]. Although CCK receptors have not been reported on hepatic stellate cells, the liver and pancreas develop from endodermal epithelium of the embryonic foregut [43] and have many common features.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their proliferative role on cancer cells, CCK receptors have been identified on pancreatic stellate cells [40] and fibroblasts [41]. Proglumide treatment decreases tumor-associated fibrosis in mouse models of pancreatic cancer [24,36,42]. Although CCK receptors have not been reported on hepatic stellate cells, the liver and pancreas develop from endodermal epithelium of the embryonic foregut [43] and have many common features.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that if gastrin signaling at the CCK-B receptor was blocked with a CCK-receptor antagonist, that fibrosis and inflammation in the tumor microenvironment is decreased significantly. 9 , 36 in part by interference with the CCK-B receptor on the pancreatic stellate cells or cancer-associated fibroblasts. Therefore, it is not surprising to find that the polyplex carrying gastrin siRNA to tumors also can alter genes associated with tumor fibrosis and inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…The GPCR can be used to direct neuropeptide coated nanoparticle to the tumor. Recently, cholecystokinin antagonists were found to potentiate the effects of immune checkpoint inhibitors at impairing the growth of pancreatic tumors in vivo ( 138 ). Thus GPCR antagonists can potentiate the effects of various drugs in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%